Analysis of aggregate particle migration properties during compaction process of asphalt mixture. (10th February 2019) - Li, Peilong; Su, Jinfei; Gao, Peng; Wu, Xu; Li, Jiange
Highlights: The step-by-step gyratory compactions were conducted. The migration properties of aggregates during the compaction process were analyzed. The migration indexes and rolling indexes were respectively proposed. The compaction process and mechanism of the asphalt mixture was discussed. Abstract: Asphalt mixture is a kind of anisotropic multiphase granular materials. The compaction is the consequence of particle rolling and migratory permutation. To anatomize the migration properties of aggregates during the compaction process of asphalt mixture, the step-by-step gyratory compactions were conducted on the asphalt mixtures with different gradations under the different test conditions, and the migration indexes encompassing L x, L y, L z, L xoy and rolling indexes encompassing α, α Δ x, α Δ y, α Δ z were proposed. The marked aggregate particles were placed in the asphalt mixtures, and their migration characteristics were observed during the gyration compaction by the X-ray CT and the images were processed adopting Image-pro premier and MATLAB. Thereupon, the migration properties of aggregates were elucidated at the micro-scale level. The results bespeak that the coarse aggregate particles located in the upper or middle layers tend to migrate down, while they located in the lower or middle layers tend to migrate horizontally and tend to roll easy and the rolling occurs mostly in the horizontal direction. The contribution of mixture gradation and asphalt binder to the migration properties of aggregates are different in different compaction stages. In the early stage of compaction, the aggregate gradation, percentage of coarse aggregate and particle characteristics play dominant roles in aggregate particle migration. At the same time, asphalt binder also exerts an influence on lubrication action and cementation action between the particles, resulting in different migration properties. With the compaction progressing, the mixtures tend to be dense, and the fine aggregate migration is the main factor for further compaction of the mixtures.